Comparison of mechanical properties between Nice knot, Modified Nice knot, and surgeon's knot. (December 2021) - Friedman, Lisa G.M.; Quigley, Ryan; Shewman, Elizabeth; Kirsch, Jacob; Freehill, Michael T.; Garrigues, Grant E.
Abstract: Background: The success of surgical repairs rely on the effectiveness and integrity of the surgical knots used to secure the repair. The purpose of this study is to examine and compare the performance of the Nice knot, the modified Nice knot, and a commonly used combination of surgeons' and square knots with respect to cyclic loading and load-to-failure usiflueng a high-strength suture composed of ultra-high molecular weight polyethylene in the hands of experienced surgeons. Methods: Two experienced surgeons threw 3 different knot types 9 times, consisting of the Nice knot, modified Nice knot, and a surgeon's knot utilizing Ultrabraid #2 sutures. Each knot was subject to cyclic loading and load to failure testing. Findings: Both surgeons had similar displacement data for the surgeon's knot, while the identity of the surgeon impacted displacement for the Nice knot ( p = 0.03) and the modified Nice knot ( p = 0.0002). The load to failure for the modified Nice knot ( p < 0.001) and the Nice knot ( p = 0.001) were significantly impacted by the surgeon tying the knot, while the surgeon's knot was not. Specimens failed where the sutures passed through the loop at the "base" of the knot. Interpretations: The strength and integrity of complex surgical knots are variable between surgeons. While the proposed Modified Nice Knot has a theoretical advantage because the half hitches reinforce the primary knot, in load to failure testing both the Modified Nice Knot and the Nice Knot failed where the suture passed through the loop in the primary knot. Highlights: The strength of knots are variable between surgeons between the Nice and modified Nice knot. The integrity of knots are variable between surgeons between the Nice and modified Nice knot. Both Nice knot types failed where the suture passed through the loop in the primary knot. The surgeon's knot had similar displacement and load to failure results.